Dynamical reorganization of the pluripotency transcription factors Oct4 and Sox2 during early differentiation of embryonic stem cells - Verneri, Paula (2020)
Pluripotency maintenance requires transcription factors (TFs) that induce genes necessary to preserve the undifferentiated state and repress others involved in differentiation. Recent observations support that the heterogeneous distribution of TFs in the nucleus impacts on gene expression. Thus, it is essential to explore how TFs dynamically organize to fully understand their role in transcription regulation. Here, we examine the distribution of pluripotency TFs Oct4 and Sox2 in the nucleus of embryonic stem (ES) cells and inquire whether their organization changes during early differentiation stages preceding their downregulation. Using ES cells expressing Oct4-YPet or Sox2-YPet, we show that Oct4 and Sox2 partition between nucleoplasm and a few chromatin-dense foci which restructure after inducing differentiation by 2i/LIF withdrawal. Fluorescence correlation spectroscopy showed distinct changes in Oct4 and Sox2 dynamics after differentiation induction. Specifically, we detected an impairment of Oct4-chromatin interactions whereas Sox2 only showed slight variations in its short-lived, and probably more unspecific, interactions with chromatin. Our results reveal that differentiation cues trigger early changes of Oct4 and Sox2 nuclear distributions that also include modifications in TF-chromatin interactions. This dynamical reorganization precedes Oct4 and Sox2 downregulation and may contribute to modulate their function at early differentiation stages.